2019
DOI: 10.1371/journal.pone.0224082
|View full text |Cite
|
Sign up to set email alerts
|

Role of rhesus macaque IFITM3(2) in simian immunodeficiency virus infection of macaques

Abstract: The experimental infection of rhesus macaques (rh) with simian immunodeficiency virus (SIV) is an important model for human immunodeficiency virus (HIV) infection of humans. The interferon-induced transmembrane protein 3 (IFITM3) inhibits HIV and SIV infection at the stage of host cell entry. However, it is still unclear to what extent the antiviral activity of IFITM3 observed in cell culture translates into inhibition of HIV/SIV spread in the infected host. We have shown previously that although rhIFITM3 inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Vice versa it was also shown that primate IFITMs are effective against human viruses (69,70), in line with the high degree of conservation of IFITMs in primate species (71,72).…”
Section: Discussionmentioning
confidence: 87%
“…Vice versa it was also shown that primate IFITMs are effective against human viruses (69,70), in line with the high degree of conservation of IFITMs in primate species (71,72).…”
Section: Discussionmentioning
confidence: 87%
“…[ 26 ] IFITM3, an interferon-inducible transmembrane protein, has been found to exert an inhibitory effect against HIV and simian immunodeficiency virus infection during the host cell entry phase. [ 27 ] This cytokine reduces HIV-1 infectivity through a mechanism that is not fully understood. [ 28 ] Furthermore, IFITM proteins, and in particular IFITM3, can bind with HIV-1 viruses and inhibit their fusion and cell-to-cell transmission.…”
Section: Discussionmentioning
confidence: 99%